O impacto do Instituto Federal de Educação, Ciência e Tecnologia do Ceará na qualidade do mercado de trabalho nos municípios do Ceará - Marques, Dirlândia de Oliveira (2017)
This work study aims to evaluate the impact of the Federal Institute of Education, Science and Technology of Ceará on the quality of the labor market in the municipalities of Ceará using the methodology of differences in differences. The treatment group is made up of the municipalities of Baturité, Canindé, Morada Nova and Tabuleiro do Norte, because they have IFCE campuses that had their first graduates between 2011 and 2013. Taking into account the full treatment group, it was decided to evaluate the effect of the program on the labor market in 2014, in order to capture the treatment effect. The quality of the labor market was measured by observing the number of full-time jobs for people with vocational education during high school and for people with higher education in relation to the total number of formal jobs in the pre-treatment period in 2010 and after treatment in 2014. The data was obtained from the Annual Listing for Social Information (Rais) of the Brazilian Ministry of Labor and Employment (MTE). The result showed that the implementation of the IFCE campuses in the municipalities of Baturité, Canindé, Morada Nova and Tabuleiro do Norte did not contribute to the quality of the labor market in these municipalities.